Pirólise de gás natural veicular com dióxido de carbono em uma tocha de plasma tipo tornado - Ribeiro, Rafael Pires (2015)
This paper evaluates the pyrolysis of Vehicular natural gas (GNV) with CO2 via a “tornado” gliding Arc plasma. This system type begins in thermal plasma and then evaluate to the non-thermal regime, with low current and high voltage under atmospheric pressure. Typically, this plasma has low power. The transient behavior is capable to stimulating chemical reactions in present gases, needn’t to heat it. At this work, it was developed in the laboratory a tornado plasma torch with copper electrodes, and a power supply of 7 kV with 80 mA. Parallel to the experimental development, it was made a plasma torch simulation by a computational fluid dynamics (CFD), which showed very similar results with the real torch behavior. It was realized seven tests that gas flow rates and anode diameter were varied. Flow rates were adjusted for the arc stability, which is relied heavily with the anode diameter. It was observed that, the decreased diameter of the anode allowed to increase the GNV / CO2 ratio and increased energetic efficiency in the H2 production. The maximum energetic efficiency was obtained for the anode with 5,0 mm of diameter, getting (11 ± 3) mol H2 per kW.h. This result is twice the amount reported in the literature by Xumei Tao (2011), and is equivalent to the results of thermal plasma torches, that have twice energetic efficiency in relation to the gliding arc. During testing, the GNV / CO2 ratio became higher than 1, there may be a situation that have a solid carbon production. This was verified at the end of work. The solid sample was characterized by scanning electron microscopy and X-ray diffraction, which demonstrated the presence of Graphitized and amorphous materials such as carbon black. The negative factor was the presence of CO2 gas in the final composition, since CO2 requires a higher temperature to be decomposed than CH4.